New PRSS1 and common CFTR mutations in a child with acute recurrent pancreatitis, could be considered an "Hereditary" form of pancreatitis ? - Corleto, Vito D (BioMed Central, 2010)
BACKGROUND: acute recurrent pancreatitis is a complex multigenic disease, the diagnosis is even more difficult when this disease develops in a child. CASE PRESENTATION: a 6-years old boy, hospitalized with epigastric pain radiating to the back showed high serum levels of serum amylase, lipase, CRP and erythrosedimentation rate. Several similar milder episodes of pain, followed by quick recovery and complete disappearance of symptoms were reported during the previous 13 months. The child was medically treated and after 7 days with normal clinic and laboratory tests was discharged with a hypolipidic diet. All the known aetiologic hypotheses were excluded by anamnestic investigation, clinical observation and biochemical evaluation, whereas, anatomic abnormality were excluded by a secretin stimulated magnetic resonance (MRI). At the last follow-up visit, (11 months later), the child showed a normal body weight and anthropometric profile, without further abdominal pain. Mutation screening for coding regions of PRSS1, SPINK1, CFTR and the new hereditary pancreatitis-associated chymotrypsin C (CTRC) genes showed a novel variation, c.541A > G (p.S181G), in the exon 4 of PRSS1 gene and the classical CF p.F508del mutation in the CFTR. Both mutations were present in his clinically normal mother and absent in the patient's father. CONCLUSIONS: this report extend the spectrum of PRSS1 mutations, however, the absence of family history of pancreatitis leaves the present case without the hallmark of the hereditary origin of pancreatitis. At the present knowledge it can be only stated that the combined genotype CFTR (F508del)/PRSS1 (S181G) is associated to a mild phenotype of acute recurrent pancreatitis in this child without any further conclusion on its pathogenetic role or prediction on the course of the disease.